WATER LEACHING OF CESIUM FROM SELECTED CESIUM MINERAL ANALOGUES - Klika Z.; Weiss Z.; Mellini M.; Drábek M. (My University, 2006)
Recently, a new mica phase Cs-tetra-ferri-annite has been synthesized and studied. This phase has been investigated because its high structural stability and assumed associated low leachability for Cs suggest that it may be a suitable waste form for immobilization of Cs. Further, synthesis, under hydrothermal conditions, is possible under conditions typical of an industrial-scale immobilization plant. Consequently, cesium-tetra-ferri-annite can be considered as a waste form for the fixation of Cs from solid radioactive waste. In this study, Cs immobilization in Cs-tetra-ferri-annite and CsAlSiO4, as well as sorption onto montmorillonite and zeolite 13X, have been studied. Experiments were carried out to determine the influence of pH, temperature, time and leaching technique on the extent of release of Cs from these solids. These leaching studies have confirmed the limited leachability of Cs-tetra-ferri- annite, which was found to be more stable than CsAlSiO4 by a factor of 3.7 at ambient temperature and near-neutral pH. These waste forms have also been found to be more effective in retaining Cs than Cs-montmorillonite and Cs-zeolite 13X. The relative release of Cs from all of the studied phases exhibits a similar trend with pH, temperature, time and techniques of leaching used in this study. For these phases, the leachability of Cs increases with acidity (pH 3) or alkalinity (pH 11) of the leachates as well as with increasing temperature and time of leaching. For CsAlSiO4, the Cs-leachability was most strongly affected by increasing temperature. Cesium releases from this phase increased by a factor of about 6 when the temperature was raised from 20 to 100°C. This increase with temperature was 3-6 times higher than that measured for the other phases. Under the present leaching conditions, Cs is released more than the matrix elements. Elements present in tetrahedral positions of CsAlSiO4, Cs-montmorillonite and Cs-zeolite 13X leach much easier than elements in octahedral positions. © 2006 Elsevier Ltd. All rights reserved.